An Evaluation on the Effects of Language-Literature and History-Museum Branches of Community-Houses on Cultural Heritage of Turkey - AKBAŞ, GAMZE (Deniz Yengin, 2019)
Community Houses are important institutions that operate for public awareness with the establishmentof the Republic of Turkey. In this context, it is aimed to discuss the activities of the CommunityHouses for protection of our cultural heritage through “Language and Literature” and “History andMuseum” branches. The aim of the study is to offer an evaluation, which contributes to the activitiesof both branches, basing the role of Community Houses upon protection of our tangible and intangiblecultural assets. While examining public knowledge and linguistic issues as part of duties andresponsibilities of the “Language and Literature” branch, studies on excavation, conference, museumbuilding, restoration and preservation of ancient monuments were analysed by the “History andMuseum” branch. In this direction, a literature review was made on cultural heritage studies that hadbeen carried out by the Community Houses until 1951, predominantly between 1933 and 1935. Wehave reached some information demonstrating that people realized the importance of the culturalinventory and adopted the consciousness of protecting the national values and studies on art, history,archeology increased. It has been determined that the “Language and Literature” branch tried to instila consciousness of national culture and emphasize the language issue throughout the country.Excavations, ethnography and historical researches have been carried out with the works of the“History and Museum” branch.

Halkevleri, Türkiye Cumhuriyeti’nin kurulmasıyla birlikte halkın bilinçlenmesi için faaliyet gösteren önemli bir kurumdur. Bu bağlamda Halkevlerinin kültür mirasımızı korumaya yönelik faaliyetlerinin, “Dil ve Edebiyat” ile “Tarih ve Müze” şubeleri üzerinden tartışılması amaçlanmıştır. Araştırmanın hedefi, Halkevlerinin rolünü somut ve somut olmayan kültürel varlıklarımızın korunması ilişkisine dayandırarak, her iki şubenin faaliyetlerine yönelik katkı sağlayan bir değerlendirmenin sunulmasıdır. “Dil ve Edebiyat” şubesinin görev ve sorumlulukları kapsamında halk bilgisi ve dil konuları incelenirken, “Tarih ve Müze” şubesinde kazı, konferans, müze kurma, eski eserlerin onarılması ve korunmasına yönelik çalışmalar analiz edilmiştir. Bu doğrultuda, Halkevleri tarafından ağırlıklı olarak 1933-1935 olmak üzere 1951 yılına kadar yürütülen kültür mirasına yönelik çalışmalar üzerine literatür taraması yapılmıştır. Her iki şube vasıtasıyla kültür envanterinin önemi, milli değerleri koruma bilincinin halka benimsetilmesi ve sanat, tarih, arkeoloji gibi alanlarda çalışmaların artmasını gösteren bilgilere ulaşılmıştır. “Dil ve Edebiyat” şubesinin yurt genelinde milli kültür bilincini aşılamaya çalıştığı ve dil meselesi üzerinde önemle durduğu tespit edilmiştir. “Tarih ve Müze” şubesinin çalışmalarıyla kazı, etnografya ve tarihi araştırmalar gerçekleştirilerek, Anadolu tarihinin kayda değer şekilde aydınlatıldığı görülmüştür.
Halkevleri̇ Di̇l-Edebi̇yat ve Tari̇h-Müze Şubeleri̇ni̇n Kültür Mi̇rasimiza Etki̇leri̇ Üzeri̇ne Değerlendi̇rme
Keywords: Community Houses; Language and Literature Branch; History and Museum Branch; Cultural Heritage